Uso De Las Tics Y Objetos De Aprendizaje Para La Enseñanza De Las Matemáticas En La UCPR (2019)
This article presents the development and implementation of an active strategy supported on the technologies for communication and information, which make it easier the teaching and learning process among teachers and students in the classroom. That strategy will befocused specifically on those students who are taking mathematics courses in the different academic programs at Universidad Católica Popular del Risaralda. The main objective with this project is that the students improve their knowledge about this area and develop the minimal competences related to the subject. As it is mentioned in the National Plan on technologies for communication and information, “the use of these technologies has changed the social customs and the way people interact. They have improved the opportunities for many people who were traditionally excluded, and the social mobility has been increased. These technologies have also changed the way people learn and the role of teachers and students. It has also demonstrated that the learning process cannot be measured in terms of time, it must be developed along the life of each person”. It is important to remark that technologies for communication and information are a resource for the improvement of the teaching practice, but taking into consideration the human being. This is the reason why, the methodology proposed is based on the institutional ethic andeducative principles, looking forward pedagogic theory, pedagogical practice, and the use of technologies for communication and information applied for the teaching and learning process of mathematics, will contribute to get as a result, students who will become people, professionally and capable people.